THE ROLE OF MENTAL PRACTICE AND TECHNOLOGY IN TRADITIONAL VIOLIN TEACHING AND LEARNING - Uğur ÇİT (International Journal of Eurasia Social Sciences, 2023)
Music is a creative art that requires spontaneous emotional expression. This art necessitates proficiency with musical instruments, such as the violin. Despite the fact that the approaches for advancing the skill of violin playing are generally recognized, new teaching methods have emerged as a result of the Internet and technological breakthroughs. Based on this context, this study aims at examining how the advances on the Internet and technology are affecting violin education and learning, and accordingly, the effects of YouTube, an online Web 2.0 tool, and Suzuki and Zhang's audio and online video teaching methods on violin education. Document analysis, a qualitative research method, was used in the research methodology. As the working document of the research, the teaching techniques of violin instructors who use the traditional approach method for the applicability of new learning approaches in violin education were analyzed, and their individual teaching experiences were discussed. The results of these experiences show that there is a consensus regarding the significance of mental practice in developing mind-body coordination during the initial stages of learning to play the violin. The research findings demonstrate that the online method, one of Suzuki and Zhang's technological approaches, lags behind the traditional approach method. It was found that technological approaches, in particular, are insufficient in meeting the needs of students in violin education and in guiding the learning development of their mental practices. However, YouTube has also been deemed significant because it allows students to view masterclasses and performances by renowned musicians and orchestras.